Driving Green Creativity Through Leadership, Green HRM, and Employee Voice: A Study in Automotive Industry - Ratna Kurniasari; Aryana Satrya (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of green inclusive leadership (GIL) and green human resources management (GHRM) on green creativity (GC), with green voice behavior (GVB) as a mediating variable. The primary focus is to examine the extent to which GIL and GHRM can foster employees’ green creativity through GVB. This research employs a quantitative approach using a survey method distributed to employees in an automotive manufacturing company in Indonesia. The study was conducted on 389 employees of the one of automotive company market leader in Indonesia using a purposive sampling technique. Data processing and analysis are conducted using Covariance-Based Structural Equation Modelling (CB-SEM). The originality of this research lies in the integration of GIL and GHRM, variables that have not been extensively explored within the context of Indonesia’s automotive industry, with GVB as a mediator. The findings of this study indicate that GIL has a positive and significant effect on GC through the full mediation of GVB. GHRM has a direct positive and significant effect on GC, as well as an indirect effect through the mediation of GVB.